Pediatric dental practice during, pre and post COVID-era: a literature review - Gautam, Kanishka; Srivastava, Nikhil; Rana, Vivek; Kaushik, Noopur; Pruthi , Tushar (International Journal Of Community Medicine And Public Health, 2024)
Everyone is on edge for their health and safety as the COVID-19 pandemic has hit both developed and developing countries. As a result of its fast transmission rate by direct touch or droplet dispersion, the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major concern for healthcare practitioners and is responsible for the horrific 2019 coronavirus sickness (COVID-19). An extensive electronic search was conducted using Google Scholar, PubMed, Scopus MEDLINE, EMBASE, Web of Science, Scopus, and Google to investigate the COVID-19 epidemic and its impact on pediatric dentistry. Pediatric dentists still do not have access to full data that would allow them to treat their pediatric patients before, during, and after the pandemic, despite the fact that more information is accessible on the concerning progression of COVID-19.